CLASSIFICATION OF MORPHEMIC UNITS ACCORDING TO FUNCTION (Scientific journal of the Fergana State University, 2023)
This article describes the changes in the classification of types, suffixes according to the function of morphemic units. Explanations of naming of word-forming, relational forms, lexeme forming morphemes are given.